Penguatan Kelembagaan Desa Wisata melalui Promosi Digital Marketing di Desa Cisaat, Kecamatan Ciater, Kabupaten Subang - Jenal Abidin; Rezka Fedrina; Revi Agustin (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2022)
Strengthening Tourism Village Institutions through Digital Marketing Promotion in Cisaat Village, Ciater District, Subang Regency An increase in the number of tourist visits to a destination is an indicator of the success of an effective marketing promotion strategy. The selection of an effective marketing promotion strategy that is in accordance with market trends is an absolute must. One of the effective media in the promotion of destination marketing is to use digital marketing media. Cisaat Tourism Village, Subang is one of the villages that makes tourism one of the sectors that drive the economy of its people. Cisaat Tourism Village has considerable potential including cultural tourism, nature tourism and educational tourism. Cisaat Tourism Village has a weakness in terms of marketing promotion so that the increase in the number of visits is not significant. Community service programs are expected to be the solution. The activities carried out were workshops on making tourist village websites, digital marketing workshops to increase knowledge and skills regarding interesting content for website marketing and social media marketing. The output of this activity is the availability of a marketing promotion website for tourism village packages, the skills of tourism village managers in creating social media marketing promotional content.